Zipf rank analysis highlights the exploration potential for Lithium-Caesium-Tantalum -type pegmatites in the Northern Cape, South Africa. (January 2023) - von der Heyden, Bjorn P.; Todd, Chad; Mayne, Matthew J.; Doggart, Shane
Abstract: Exploration activities for mineralised Lithium-Caesium-Tantalum (LCT) pegmatites in the metalliferous Orange River pegmatite belt (southern Africa) are hampered by a dearth of any reasonable estimates of the mineral province's residual metal endowment or of its prospectivity. To mitigate this, Zipf rank analysis has been used to estimate the likelihood of pegmatites occurring below Quaternary cover sediments which veneer extensive tracts of this mineral province. The Zipf rank analyses focused on the western extremity of the pegmatite belt near Vioolsdrif where historical mining activities have exploited several pegmatite bodies including the world-class Li–Bi–Be–Cs–Ta-mineralised Noumas 1 pegmatite. Zipf rank analyses were conducted on the surface exposures of both a comprehensive dataset of mineralised- and unmineralised pegmatites (N = 159), and on a subset which comprised only the mineralised pegmatites (N = 23). Results from the latter analysis indicate that up 11 500 m 2 (or ∼11%) of mineralised pegmatite surface exposure remains to be found within the confines of the defined study area. Because our Zipf analyses considered surface exposure at the present day erosional level of the Meso-proterozoic basement rocks, we suggest this residual endowment is hidden beneath the unconsolidated cover sediments. This novel application of Zipf rank analysis to pegmatite surface exposure thus highlights the prospectivity of the Orange River pegmatite belt for several of earth's critical raw materials. Graphical abstract: Image 1 Highlights: First application of Zipf rank analysis towards understanding pegmatite exposures. Moderate exploration potential for mineralised pegmatites in the N. Cape (RSA). Possible exploration targets on post-African 1 surface below recent sediment veneer.